Phytonutrient formulation using gum Arabic and Adansonia Digitata pulp: Lessons for boosting the human immune system - part 1 - Elnour, Ahmed A.M.; Nour, Abdurahman Hamid (Elsevier B.V., 2024)
Background: The human innate immune system (HIIs) defends the body against pathogens and relies on the energy obtained from food sources to increase its metabolic activity. Aim: In this study, a new blended 3 in1 formula comprising A. senegal, A. seyal, and Adansonia digitata at a ratio of 5:3:2 was proposed as a potential aid in the management of Covid-19 patients with Metabolic Syndrome (MeT-S) disorders, with a specific focus on those presenting with impaired health. Methods; The utilization of Inductively Coupled Plasma-Optical Emission Spectroscopy (ICP-MS) was employed to analyze 3 blended ingredient combinations, including the 3in1 formula, A. senegal, A. seyal, and A. digitata pulp, for the presence of elements by detecting the levels of moisture, ash, minerals, protein, amino acids, carbohydrates, sugars, prebiotic polysaccharides, energy, dietary fibers, and crude fibers. This advanced technique has replaced the titration method used in previous studies. Results: The mineral content of the blended 3in1 sample was found to be dominated by potassium (70.56±2.35), Calcium (68.54±3.12), Magnesium (16.60±4.80), Phosphorus (11.50±2.50), Sodium (31.4±4.80), Zinc (19.19±2.10), Iron (19 ± 0.14), Copper (15.12±1.81), and selenium (0.037 ± 0.005) g/100 g DW. The blended 3 in1 sample also had a higher hydroxyproline content (30.17 g/100 g and a higher total protein and carbohydrate content than the blended 2 in1 sample. Additionally, arabinose was identified as the major reducing sugar with up to 48.23 and 49.97g/100 gDW. The prebiotic polysaccharide content was 88.61±3.12g/100 gDW for the blended 3 in1 sample, which was significantly higher than that of the blended 2 in1 sample. Furthermore, the energy value of the blended 3 in1 sample was significantly higher at 350.12±5.210 kcal/100 g than the blended 2 in1 sample at 340.67±3.155 kWh. The Insoluble Dietary Fibers (IDFs) and Soluble Dietary Fibers (SDFs) of the blended 3 in1 sample were 12.6±2.10 g/100 gDW and 87±2.124 g/100 g DW, respectively, which were significantly higher than those of the blended 2 in1 sample. Conclusion: The discovery of distinct molecular compositions of A. senegal and A. seyal when combined with Adansonia Digitata Pulp (ADLP) in the 3 in1 blend demonstrated enhanced HIIs among Covid-19 patients with compromised MeT-S disorders. This may be considered a valuable natural antiviral agent for the treatment of such individuals.